Spotlight on Ki67 as a prognostic marker in early breast cancer: all that glitters may not be gold - Roberta Maltoni; Michela Palleschi; Sara Ravaioli; Maria Maddalena Tumedei; Mattia Altini; Sara Bravaccini (BMC, 2020)
Abstract Kang and colleagues evaluated on a case series of 1848 breast cancer (BC) patients operated for a first primary ER positive HER2 negative BC if Ki67 expression is a significant prognostic factor only when PgR expression is low. The authors concluded that Ki67 with 10% cut off value is a prognostic factor only under low PgR expression level in early BC. We would like to underline, that as already stated in our previous papers, we believe that proliferation is important to define the decision-making of adjuvant therapies in early BC. The issue on Ki67 detection is the poor reproducibility due to different antibody clones, platforms and scoring methods. Not less important is that different Ki67 cut off values have been used by San Gallen guidelines and changed overtime. Then, despite the interesting results, we believe it would be better to use Ki67 biomarker in according to the standard Ki67 cut off according to San Gallen guidelines. Nowadays, standardization and optimization of Ki67 is still an urgent need.